ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DENGAN BANK SYARIAH PERIODE 2015-2019 - Ila Komalasari; Wirman Wirman (Universitas Bunda Mulia, 2021)
ABSTRACT: Even though the majority of the population of Indonesia is Muslim, there is a lack of views about the advantages of Islamic banks, so they prefer to use conventional banking services. The target to be achieved is to find out whether there is a dissimilarity between conventional banks and Islamic banks in their financial performance. And to find out which banking institution is superior based on financial performance ratios. This study uses a comparative descriptive method through a quantitative approach. The sampling technique used is simple random sampling technique. The data used are financial ratios, namely CAR, NPL/NPF, ROA, BOPO, and LDR/FDR. Then the facts are as follows: 1) There is dissimilarity in CAR performance between the two banks, and CAR at conventional banks is superior to Islamic banks. 2) There is dissimilarity in the performance of NPL/NPF between the two banks, and the NPL/NPF of conventional banks is superior to that of Islamic banks. 3) There is no dissimilarity in ROA performance between the two banks, and ROA at conventional banks is superior to Islamic banks. 4) There is no dissimilarity in BOPO performance between the two banks, and BOPO at conventional banks is superior to Islamic banks. 5) There is no dissimilarity in the performance of LDR/FDR between the two banks, and LDR/FDR in Islamic banks is superior to conventional banks.Keywords: Conventional Banks, Islamic Banks, Financial Performance, Financial Ratios ABSTRAK: Kendatipun sebagian besar penduduk negara Indonesia beragama Muslim, namun minimnya pandangan mengenai keunggulan bank syariah sehingga mereka lebih memilih memanfaatkan jasa perbankan konvensional. Sasaran yang ingin dicapai yakni ingin mendapati ada tidaknya dismilaritas bank konvensional dengan bank syariah dalam kinerja keuangannya, dan untuk mendapati lembaga perbankan mana yang lebih unggul beralaskan rasio kinerja keuangan. Penelitian ini memakai metode deskriptif komparatif melalui pendekatan kuantitatif. Dengan Teknik pengambilan sampel yang dipakai yakni teknik simple random sampling. Data yang dipakai berupa rasio-rasio keuangan yaitu CAR, NPL/NPF, ROA, BOPO, dan LDR/FDR. Kemudian faktanya yakni seperti berikut ini: 1) Adanya dismilaritas kinerja CAR antara kedua bank, dan CAR pada bank konvensional lebih unggul ketimbang bank syariah. 2) Adanya dismilaritas kinerja NPL/NPF antara kedua bank, dan NPL/NPF pada bank konvensional lebih unggul ketimbang bank syariah. 3) Tidak adanya dismilaritas kinerja ROA antara kedua bank, dan ROA pada bank konvensional lebih unggul ketimbang bank syariah. 4) Tidak adanya dismilaritas kinerja BOPO antara kedua bank, dan BOPO pada bank konvensional lebih unggul ketimbang bank syariah. 5) Tidak adanya dismilaritas kinerja LDR/FDR antara kedua bank, dan LDR/FDR pada bank syariah lebih unggul ketimbang bank konvensional.Kata Kunci: Bank Konvensional, Bank Syariah, Kinerja Keuangan, Rasio Keuangan